Design and performance study of MAC protocols in multi-hop wireless sensor networks - Nguyen, Thuy Ngoc. (2009)
Recent advancement in wireless communications and sensor technologies has enabled the development of low-cost sensor networks for diverse applications. Medium access control (MAC) protocols play a crucial role in energy-efficiency, latency reduction for sensor networks. Duty-cycle has been widely used to reduce energy consumption and shorten delay in multi-hop WSNs. While existing duty-cycle MAC protocols, such as S-MAC, are energy-efficient, they bear a long end-to-end delivery latency in multi-hop WSNs. This project aims to develop a new MAC protocol to energy-efficiently serve the data traffic and provide high performance. In this report, a new MAC protocol called Adaptive Scheduling MAC (AS-MAC) is introduced. The algorithm is designated to schedule more data packets for transmission in bursty and high traffic loads, thus enabling rapid dissemination of data and reduction of the end-to-end delivery latency. While in the light traffic loads, nodes enters the Sleep mode, mitigating idle listening and saving energy. It is shown in the simulation results that the proposed protocol is a great advancement of some existing protocols on performance, especially with heavy traffic loads while keeping the low energy consumption level.